2020
DOI: 10.1344/geologicaacta2020.18.14
|View full text |Cite
|
Sign up to set email alerts
|

Foraminifera of shallow and very shallow facies from the upper Eocene–lower Oligocene Kazandere Member, Soğucak Formation, Thrace Basin, northwest Turkey

Abstract: The middle-late Eocene to early Oligocene sediments, mainly limestone of the Soğucak Formation with its shallow water marine foraminiferal species occur most widespread in the territory of the Thrace basin. So far, the very shallow water Priabonian sediments with here described foraminiferal species have not been reported from Tharece basin. The here established Kazandere memeber of the Soğurcak Formation located between Kıyıköy andKömürköy,(NW of Kırklarel) was studied with respect to the sedimentologic as (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Although reported in previous works on the Becirman Formation (Meriç & Çoruh 1991;Çoruh et al 1997;Yılmaz & Duran 1997), no miscellaneids have been found in the investigated samples. Mi-scellanea and Miscellanites (also known from Turkey under its junior synonym Akbarina Sirel, 2009) are in fact generally widespread since the SBZ2 (e.g., Hottinger 2009;Benedetti et al 2018;Consorti & Köroğlu 2019). Probably, tangential cuts of the piles of the ventral side of Elazigina dienii have been erroneously interpreted as piles of Miscellanea in previous studies on the Becirman Formation.…”
Section: Resultsmentioning
confidence: 99%
“…Although reported in previous works on the Becirman Formation (Meriç & Çoruh 1991;Çoruh et al 1997;Yılmaz & Duran 1997), no miscellaneids have been found in the investigated samples. Mi-scellanea and Miscellanites (also known from Turkey under its junior synonym Akbarina Sirel, 2009) are in fact generally widespread since the SBZ2 (e.g., Hottinger 2009;Benedetti et al 2018;Consorti & Köroğlu 2019). Probably, tangential cuts of the piles of the ventral side of Elazigina dienii have been erroneously interpreted as piles of Miscellanea in previous studies on the Becirman Formation.…”
Section: Resultsmentioning
confidence: 99%
“…The assemblages of benthic foraminifera change from being composed mainly by hyaline forms with some porcellaneous specimens in the Eocene to a wide predominance of porcellaneous ones in the lower Oligocene ("Praerhapydionina limestones and marls" of Geel, 1995). The Rupelian porcellaneous foraminifera have been studied in sequences from the Middle East: Turkey (Sirel et al, 2013(Sirel et al, , 2020Kay gili, 2016), Oman (Serra-Kiel et al, 2016), Iran, and Iraq (Henson, 1950;Yazdi-Moghadam, 2011;Amirshahkarami, 2013;Karim & Hama, 2019). Shallow-water facies with porcellaneous larger foraminifera are rarely represented in the early Oligocene record of the western Tethys.…”
Section: Discussionmentioning
confidence: 99%
“…In the Ibi section (Fig. 2) the Eocene/Oligocene boundary (SBZ 20/21) is recognized by the last occurrence (LO) of Eocene taxa, with the LO of Orbitolites in sample Ibi-116 (Hottinger et al, 1964;Serra-Kiel et al, 1998;Sirel, 2003;Less et al, 2011;Serra-Kiel et al, 2016;Sirel et al, 2020; Dercourt et al, 2000, andMeulenkamp &Sissingh, 2003). Zakrevskaya, 2023).…”
Section: Biostratigrapymentioning
confidence: 99%
“…The shallow-marine Eocene deposits in the Biga Peninsula and the southern part of the Thrace Basin (northwest Turkey) are well known for the diverse occurrence of larger benthic foraminifers (LBF) after extensive research in the last decade (Okay et al, 2010, 2019; Özcan et al, 2010, 2018a; Less et al, 2011; Sirel et al, 2020; Yücel et al, 2020). The LBF assemblages mainly consist of hyaline forms such as nummulitids, orthophragminids, and rotaliids, and rare porcelaneous taxa (Özcan et al, 2010, 2018a; Less et al, 2011; Sirel et al, 2020; Yücel et al, 2020). Although some slight compositional differences in orthophragminid assemblages in the Thrace Basin have been recognized when compared with well-known European assemblages (e.g, Orbitoclypeus haynesi (Samanta and Lahiri, 1985) lineage not occurring in Europe), taxa present from these groups typically show a Western Tethyan affinity (Özcan et al, 2010, 2018b, 2022a; Less et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The shallow-marine Eocene deposits in the Biga Peninsula and the southern part of the Thrace Basin (northwest Turkey) are well known for the diverse occurrence of larger benthic foraminifers (LBF) after extensive research in the last decade (Okay et al, 2010(Okay et al, , 2019Özcan et al, 2010, 2018aLess et al, 2011;Sirel et al, 2020;Yücel et al, 2020). The LBF assemblages mainly consist of hyaline forms such as nummulitids, orthophragminids, and rotaliids, and rare porcelaneous taxa (Özcan et al, 2010, 2018aLess et al, 2011;Sirel et al, 2020;Yücel et al, 2020).…”
Section: Introductionmentioning
confidence: 99%